Plant growth and metabolism of exotic and native Crotalaria species for mine land rehabilitation in the Amazon - das Chagas, Hemelyn Soares; Guedes, Rafael Silva; Gastauer, Markus; Ribeiro, Paula Godinho; da Silva Lobato, Allan Klynger; Caldeira, Cecílio Frois; de Ávila, Fabrício William; dos Reis, André Rodrigues [UNESP]; Ramos, Silvio Junio (Springer Nature, 2024)
Despite its enormous benefits, mining is responsible for intense changes to vegetation and soil properties. Thus, after extraction, it is necessary to rehabilitate the mined areas, creating better conditions for the establishment of plant species which is challenging. This study evaluated mineral and organic fertilization on the growth, and carbon and nitrogen (N) metabolism of two Crotalaria species [Crotalaria spectabilis (exotic species) and Crotalaria maypurensis (native species from Carajás Mineral Province (CMP)] established on a waste pile from an iron mine in CMP. A control (without fertilizer application) and six fertilization mixtures were tested (i = NPK; ii = NPK + micronutrients; iii = NPK + micronutrients + organic compost; iv = PK; v = PK + micronutrients; vi = PK + micronutrients + organic compost). Fertilization contributed to increased growth of both species, and treatments with NPK and micronutrients had the best results (up to 257% cf. controls), while organic fertilization did not show differences. Exotic Crotalaria had a greater number of nodules, higher nodule dry mass, chlorophyll a and b contents and showed free ammonium as the predominant N form, reflecting greater increments in biomass compared to native species. Although having lower growth, the use of this native species in the rehabilitation of mining areas should be considered, mainly because it has good development and meets current government legislation as an opportunity to restore local biodiversity.
Keywords: Biological nitrogen fixation; Mining; Nitrogen metabolism; Plant nutrition